Análise de características geológico-geotécnicas das barragens dos programas PROURB- RH e PROGERIRH por meio de técnicas de geoprocessamento - Ramos, Orleani Costa (2008)
Among the actions performed to minimize the effects of drought in the Ceara state, the construction of dams have been that one of greatest impact, allied to complementary actions as the construction of canals and water stations. Among the essential researches for dam design, categorization of physical environment must be performed (location, climate, vegetation and hydrology), local geomorphology, geology and hydrogeology appraisals as well the study of characteristics of the local soils and the areas for loans of construction materials for earth dams. The objective of this work is to examine the geological-geotechnical characteristics of the dams of the PROURB-RH and PROGERIRH through geoprocessing techniques. The Ceara state is the area under study, in which a broad bibliographical research about the physical environment characteristics had been performed, as well as basic studies of dams within this project. The macro zoning was performed through the selection of 23 dams built between 1996 and 2008 by the programs PROURB-RH and PROGERIRH. Maps from the Companhia de Recursos Minerais-CPRM were used as a basis, to which were given treatment through the software ArcGIS®. As a result, 13 maps were georeferenced, and which considered local geology, sediment packages, field tests of the foundations, and soil specification of the loan area. Even though the predicted studies of the specific areas for the accomplishment of constructions can not be despised, the aid derived from this work will enable the rationalization of new geological and geotechnical investigations thus complementing the traditional and indispensable field studies